X-ray powder diffraction data for three new 3-ethylanilinium molybdates. Issue 2 (June 2020) - Rafalska-Łasocha, Alicja; Duda, Michał; Łasocha, Wiesław
Abstract : X-ray powder diffraction data for new metal-organic compounds: tetrakis(3-ethylanilinium) octamolybdate Mo8 O26 (C8 H12 N)4 [ a = 10.682(4), b = 16.589(5), c = 7.307(2) Å, α = 92.79(2)°, β = 97.99(3)°, γ = 103.89(3)°, V = 1240.27 Å 3, Z = 1, space group P− 1]; tetrakis(3-ethylanilinium) octamolybdate tetrahydrate Mo8 O26 (C8 H12 N)4 ·(H2 O)4 [ a = 18.801(7), b = 17.943(6), c = 7.334(3) Å, β = 98.50(5)°, V = 2446.99 Å 3, Z = 2, space group P 21 / m ] and bis(3-ethylanilinium) pentamolybdate Mo5 O16 (C8 H12 N)2 [ a = 34.643(6), b = 5.5796(7), c = 14.200(3) Å, β = 96.20(2)°, V = 2728.69 Å 3, Z = 4, space group I 2 /a ] are reported in this paper. The investigated compounds were synthesized from molybdic acid and 3-ethylaniline in acidic solution. In the first two cases, we obtained octamolybdates, while the last compound crystallized as pentamolybdate.